Searching for golden empires : epic cultural collisions in sixteenth-century America - Hartmann, William K. (University of Arizona Press, 2014)
"This lively book recounts the explorations of the first generations of Spanish conquistadors and their Native allies. Author William K. Hartmann brings readers along as the explorers probe from Cuba to the Aztec capital of Mexico City, and then northward through the borderlands to New Mexico, the Grand Canyon, southern California, and as far as Kansas. Characters include Hernan Cortes, the conqueror; the Aztec ruler Motezuma; Francisco Vazquez de Coronado, a famous expedition leader; fray Marcos de Niza, an explorer-priest doomed to disgrace; and Viceroy Antonio Mendoza, the king's representative who tried to keep the explorers under control. Recounting eyewitness experiences that the Spaniards recorded in letters and memoirs, Hartmann describes ancient lifeways from Mexico to the western United States; Aztec accounts of the conquest; discussions between Aztec priests and Spanish priests about the nature of the universe; Cortes's lifelong relationship with his famous Native mistress, Malinche (not to mention the mysterious fate of his wife); lost explorers who wandered from Florida to Arizona; and Marcos de Niza's controversial reports of the 'Seven Cities of Cibola.' Searching for Golden Empires describes how, even after the conquest of Mexico, Cortes remained a 'wildcat' competitor with Coronado in a race to see who could find the 'next golden empire, ' believed to lie in the north. It is an exciting history of the shared story of the United States and Mexico, unveiling episodes both tragic and uplifting"--